MASALAH PRIORITAS YANG DIHADAPI PETANI DALAM BUDIDAYA TOMAT DI DESA OEMATNUNU KECAMATAN KUPANG BARAT KABUPATEN KUPANG - Juruslan Djawa Rangga Ndima; Serman Nikolaus; Selfius P. N. Nainiti (Undana Press, 2020)
The Research with respect to determine the priority problem faced by farmers in tomato cultivation at Oematnunu Village, West Kupang Sub-District, the District of Kupang, had been conducted for five months in 2019. Objectives of this researeh are:1) to indentify characteristics of tomato cultivation applied by farmers at Oematnunu Village, West Kupang Sub-District, Kupang District; 2) to determine the priority problem faced by farmers in the cultivation of tomato crops at Oematnunu Village, West Kupang Sub-District, the District of Kupang. The research was carried out by the use of a survey method. The research location was determined purposively. In determining 43 farmers as the sample of this research, it was applied proportional random sampling from the population of 74 farmers cultivating tomato crops. To answer objective 1, data were analyzed by the use of quantitative descriptive statistics namely mean value and frequency, while to answer objective 2, data were analized by the use of guide according to McCaslin and Tibesinda cited by Hungawuwali (2016) The procedures of this guide are: (a) finding out the mean value of importance and ability score in the application of each aspect of tomato cultivation, (b) finding out the overall mean value of importance and ability score of tomato cultivation aspect, and (c) making a matrix of 2X2 which is formed by X axis and Y and straight line which is drawn through coordinate point and parallel with X axis and Y. Results of research indicated that : 1) characteristics of tomato cultivation technique applied by farmers in the research location was not in good category; and 2) the priority of problems faced by farmer in tomato cultivation at Oematnunu Village, West Kupang Sub-District, the District of Kupang is tomato cropps are attacked by disease and pest, meanwhile farmer’s ability in the application of eradication technique of disease and pest attacking tomato crops is in low level, while the level of importance in this technique is high level.